ANALISIS KINERJA KEUANGAN PADA PERUSAHAN TELEKOMUNIKASI DI BURSA EFEK INDONESIA - Ratna Sari (Jurnal Bisnis dan Kewirausahaan, 2021)
This study aims to determine the financial performance of telecommunications companies listed on the Indonesia Stock Exchange. Viewed from the Aspects of Liquidity, Solvency, Activity, and Profitability. The data used are quantitative and qualitative data. The study population is 6 telecommunication companies listed on the Indonesia Stock Exchange (IDX) in 2015-2017. The samples taken were 5 telecommunication companies listed on the Indonesia Stock Exchange (IDX). The data analysis method uses descriptive analysis using financial ratio analysis, meaning that the data obtained in the field is processed in such a way as to provide systematic, factual and accurate data on the problem under study. The results proved that PT Bakrie Telecom had a poor performance. This is evidenced by the decreasing liquidity ratio, activity ratio, and profitability ratio of the company as well as the increasing solvency ratio of the company from year to year. PT XL Axiata has a good performance. This is evidenced by the quite good liquidity ratio, solvency ratio, activity ratio, and profitability ratio even though it fluctuates up and down every year. PT Smartfren has a fairly good performance. This is evidenced by the company's good solvency ratio, activity ratio, and profitability ratio every tahunnya.PT Indosat Ooredoo has a very good performance. This is evidenced by the company's excellent liquidity ratio, solvency ratio, and profitability ratio every year. PT Telekomunikasi Indonesia has a very good performance. This is evidenced by the improvement of the company's liquidity ratio, solvency ratio, activity ratio, and profitability ratio every year.